The valediction of Moses a proto-biblical book - Dershowitz, Idan 1982-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2021)
"Moses Wilhelm Shapira's infamous Deuteronomy manuscripts -- long believed to be forgeries -- are of far greater significance than ever imagined. Idan Dershowitz shows that the text preserved in these manuscripts is not based on the book of Deuteronomy. On the contrary, it is a proto-biblical book, the likes of which has never before been seen."
Literaturverzeichnis: Seite 175-184
Keywords: Shapira, Mozes Ṿilhelm -- 1830?-1884; Shapira, Mozes Ṿilhelm - 1830?-1884; Shapira, Mozes Vilhelm - 1830?-1884; Bible -- Manuscripts; Bible; Bible - Criticism, Textual; Bible - Manuscripts, Hebrew; Manuscripts, Hebrew; Paleography, Hebrew; Manuscrits hébraïques; Paléographie hébraïque; Manuscripts, Hebrew; Paleography, Hebrew; Manuscripts, Hebrew - History; Manuscripts, Hebrew - Translations into English; Hebrew language, Biblical - Terms and phrases; Manuscripts; Aufsatzsammlung